DIGITALIZATION AND ORGANIZATION OF CARE: THE CASE OF ONCOLOGY - THIELSCHER, Christian; KAPPLER, Karolin (Journal of European Economy, 2023)
Recently, many industries have seen disruptive changes due to the rapid progress in information and communication technology (ICT). This systematic literature review aimed to develop an initial understanding of what is known about new ICT in medicine and its disruptive potential. Since medicine is organized into subsectors, we focused on oncology. Medline and Google Scholar were searched for relevant literature. We also hand-searched relevant journals not included in these databases. Retrieved articles were categorized and analyzed according to content evaluation methods. Articles from 2008 to 2021 in German and English were considered. 3,848 manuscripts were identified; after the application of inclusion/exclusion criteria, 30 articles were included in the analyses. The majority of articles (26) used a non-experimental design or detailed expert opinion. We found 10 major categories articles dealt with, ranging from the future role of physicians and the patient’s role to the purpose of ICT usage. Authors commented on many important topics that could change the organization of care massively; in almost all articles, there is significant disagreement about likely future development. ICT is becoming increasingly important in oncology and may impact both patients’ lives and professional conduct. When looking into ICT, doctors have focused on new diagnostic and therapeutic procedures but rarely on their disruptive potential. We recommend healthcare professionals to put more effort into the investigation of whether ICT changes the way oncology is performed and who is in control of this process, and to engage in shaping the future of oncology. JEL: I10, O320.